HIV Presenting as Young-Onset Dementia. (March 2014) - Verma, Rohit; Anand, Kuljeet Singh
With the advent of retroviral therapies, the incidence of severe dementia associated with HIV has been reduced, although minor neurocognitive impairment is being increasingly recognized in the course of illness. We report a case of a young woman presenting with HIV-associated dementia and raise awareness of its presentation in young age and as the first presenting symptom.